2023
DOI: 10.3390/jof9080811
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Optimization for Shiitake (Lentinula edodes (Berk.) Pegler) Mushroom Production in Ethiopia

Buzayehu Desisa,
Diriba Muleta,
Tatek Dejene
et al.

Abstract: Edible mushrooms are seen as a way of increasing dietary diversity and achieving food security in Ethiopia. The aim of this study was to develop substrates using locally available agro-industrial by-products and animal manures to enhance the production of Shiitake (Lentinula edodes) mushrooms in Ethiopia. The hypothesis was L. edodes mushroom production on seven different substrates: 100% sugarcane bagasse (S1), 80% sugarcane bagasse, 20% cow dung (S2), horse manure (S3), chicken manure (S4), cottonseed hulls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…The protein content of shiitake 3782 ranged between 2.7 % and 8.7 %. This range was lower than those mentioned by Desisa et al [ 12 ]: 13.7–19.6 %, Gaitán-Hernández et al [ 20 ]: 12.4–17.2 %, and Rahman and Choudhury [ 67 ]: 20–23 % for different shiitake strains cultivated on various agricultural wastes. Mushrooms are regarded as a valuable source of protein from a nutritional point of view.…”
Section: Resultscontrasting
confidence: 58%
See 2 more Smart Citations
“…The protein content of shiitake 3782 ranged between 2.7 % and 8.7 %. This range was lower than those mentioned by Desisa et al [ 12 ]: 13.7–19.6 %, Gaitán-Hernández et al [ 20 ]: 12.4–17.2 %, and Rahman and Choudhury [ 67 ]: 20–23 % for different shiitake strains cultivated on various agricultural wastes. Mushrooms are regarded as a valuable source of protein from a nutritional point of view.…”
Section: Resultscontrasting
confidence: 58%
“…It was noted that a minimum of 25:1 and a maximum of 55:1 C/N ratios are required for shiitake growth [ 59 ]. Desisa et al [ 12 ] found higher total yields of shiitake on substrates with a low C/N (20.96). However, in the current experiment, higher total yields were obtained on substrates with higher C/N ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation